Islamisasi materi pembelajaran Kebutuhan dan Kelangkaan pada mata pelajaran Ekonomi Sekolah Menengah Pertama - Ramadhan, De Aulia (Tawazun: Jurnal Pendidikan Islam, 2022)
This textbook research is structured with the formulation of the problem: first, what are the verses contained in the Need and Scarcity material in the Economics subject contained in the Integrated Social Sciences Textbook for Class VII junior high school. Second, analyze the materials of Need and Scarcity in the Economics subject contained in the Integrated Social Studies Textbook for Class VII SMP in accordance with Islamic and National goals. Third, how is the material for Needs and Scarcity in Economics subjects contained in the Ideal Social Sciences Textbook for Class VII SMP based on the Qur'anic Verses and the goals of Islamic Education. This study aims to: First, identify the verses contained in the material Needs and Scarcity in Economics subjects contained in the Integrated Social Sciences Textbook Class VII SMP. Second, analyze the materials of Need and Scarcity in the Economics subject contained in the Integrated Social Studies Textbook for Class VII SMP in accordance with Islamic and National goals. Third, analyze the material of Need and Scarcity in the Economics subject contained in the Ideal Social Sciences Textbook for Class VII SMP based on the Qur'anic Verse and the objectives of Islamic Education. The results of the research show: 1) In the Integrated Social Sciences Textbook Class VII Economics Sub Chapter compiled by Anwar Kurnia, there are no verses from the Koran regarding needs, scarcity, motives, actions and economic principles, etc. 2) The author does Islamization of teaching material needs and scarcity in various ways, among others: first, providing an introduction that contains advice on faith, secondly inserting relevant verses from the Koran and Hadith, third correcting economic concepts that are contrary to Islamic values. Fourth, include the work of Muslim scientists in economics. Abstrak Penelitian buku teks ini disusun dengan rumusan masalah: pertama, ayat apa sajakah yang terkandung dalam materi Kebutuhan dan Kelangkaan pada mata pelajaran Ekonomi yang terdapat pada Buku Teks IPS Terpadu Kelas VII SMP. Kedua, apakah materi Kebutuhan dan Kelangkaan pada mata pelajaran Ekonomi yang terdapat pada Buku Teks IPS Terpadu Kelas VII SMP sesuai dengan tujuan Islam dan Nasional. Ketiga, bagaimana materi Kebutuhan dan Kelangkaan pada mata pelajaran Ekonomi yang terdapat pada Buku Teks IPS Terpadu Kelas VII SMP yang Ideal berdasarkan Ayat Alquran dan tujuan Pendidikan Islam. Penelitian ini bertujuan untuk: Pertama, mengidentifikasi ayat yang terkandung dalam materi Kebutuhan dan Kelangkaan pada mata pelajaran Ekonomi yang terdapat pada Buku Teks IPS Terpadu Kelas VII SMP. Kedua, menganalisis materi Kebutuhan dan Kelangkaan pada mata pelajaran Ekonomi yang terdapat pada Buku Teks IPS Terpadu Kelas VII SMP sesuai dengan tujuan Islam dan Nasional. Ketiga, menganalisis materi Kebutuhan dan Kelangkaan pada mata pelajaran Ekonomi yang terdapat pada Buku Teks IPS Terpadu Kelas VII SMP yang Ideal berdasarkan Ayat Alquran dan tujuan Pendidikan Islam. Hasil penelitian menunjukkan: 1) Di dalam buku teks IPS Terpadu Kelas VII Sub Bab Ekonomi yang disusun oleh Anwar Kurnia, belum terdapat ayat-ayat Alquran mengenai kebutuhan, kelangkaan, motif, tindakan dan prinsip ekonomi, dll. 2) Penulis melakukan islamisasi terhadap materi ajar kebutuhan dan kelangkaan dengan berbagai cara, antara lain: pertama, memberikan pengantar yang berisikan nasihat-nasihat keimanan, kedua memasukkan ayat Alquran dan Hadits yang relevan, ketiga mengoreksi konsep ekonomi yang bertentangan dengan nilai-nilai Islam, keempat memasukkan kiprah ilmuwan muslim dalam ekonomi.